Pengaruh Metode Multisensori VAKT (Visual, Auditory, Kinesthetic, Tactile) terhadap Kemampuan Pengetahuan Abjad Siswa SD - Sani, Mutiara Nabila Purnama; Kusumaningrum, Syams; Asrul (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to determine the effect of using the Multisensory VAKT (Visual, Auditory, Kinesthetic, Tactile) Method  on the Alphabet Knowledge Ability of Class II Students at SDN 42 Sorong City. This research uses a pre-experiment quantitative research method with a One Group Pretest Posttest research design. The data in this study were analyzed using inferential statistical analysis techniques (Paired Sample T-test). The pretest results showed that the majority of students' alphabet knowledge at the start of the research was still in the "Low Scores'' category and after being treated with post-test results from the total sample, the majority of students were in the "Good" category. So it can be concluded that there is a significant influence of the Multisensory VAKT (Visual, Auditory, Kinesthetic, Tactile) Method on the Alphabet Knowledge Ability of Class II Students at SDN 42 Sorong City.